Growth of Women Education in Colonial India (International Journal of Scientific Research in Science and Technology, 2024)
This study delves into the history of women’s education and social reform in colonial India, shedding light on the influential figures, movements, and societal changes that shaped the status of women during this transformative period. It explores the early advocates of women’s education and reform, such as Mahadev Govind Ranade and R.G. Bhandarkar, and their contributions to the Prarthana Samaj movement. Widow remarriage, a pivotal social reform, is examined in detail, with a focus on Ranade’s role in promoting it. The study also highlights the crucial roles played by women in these reform movements, including figures like Ramabai Ranade and Tarabai Shinde. Additionally, it delves into the evolution of women’s education, challenges faced, and the changing attitudes toward women’s rights. The study underscores the significant influence of nationalism on women’s participation in the freedom struggle, with Mahatma Gandhi emerging as a champion of women’s rights. It explores the emergence of feminist consciousness through women’s journals and how education served as a catalyst for societal change. By examining these historical contexts, this study contributes to a comprehensive understanding of the progression of women’s education and empowerment in colonial India.